2008
DOI: 10.1093/humrep/den005
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of ovarian function damage by a GnRH analogue during chemotherapy in Hodgkin lymphoma patients

Abstract: Study showed a significant reduction of ovarian failure risk in women with HL treated with less aggressive CHT regimens plus a GnRH analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 23 publications
5
18
0
2
Order By: Relevance
“…These patients are in the greatest risk of chDOR and also other means of fertility preservation as oocyte/embryo or ovarian tissue cryopreservation should be offered to them prior initiation of chemotherapy, if possible. Our observations are consistent with previous studies that also indicated limited or no protection of the ovarian follicle pool with GnRH-a in young women treated with EB chemotherapy -regimen C in our study [13,17].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These patients are in the greatest risk of chDOR and also other means of fertility preservation as oocyte/embryo or ovarian tissue cryopreservation should be offered to them prior initiation of chemotherapy, if possible. Our observations are consistent with previous studies that also indicated limited or no protection of the ovarian follicle pool with GnRH-a in young women treated with EB chemotherapy -regimen C in our study [13,17].…”
Section: Discussionsupporting
confidence: 93%
“…Previously published studies report a high percentage of women with chDOR after treatment of HL, if no GnRH-a protection is received. In our previous studies, we recorded 71.0 % cases of chDOR 1 year after the end of chemotherapy [13]. Dann et al confirmed a 40.0 % chDOR rate in 4 years follow-up time [21].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…There were unexpectedly high incidences of POF in the control group in two larger studies by Castelo-Branco et al and Huser et al 46,47 The expected rate of POF in the population not treated with GnRH agonists is usually in the region of 32-37%, as found in other studies on Hodgkin's lymphoma survivors. 50,51 The high POF rate in the control group in the two larger studies influences any meta-analysis currently performed.…”
Section: Clinical Studies On Ovarian Suppression and Protection Againmentioning
confidence: 74%
“…However, until confirmatory studies are completed, the cutoff of 10 Gy will be referenced in our discussion of radiation sensitization. It has already been demonstrated that induction of gonadal inhibition by treatment with LHRH agonists or antagonists can reduce the deleterious effects of chemotherapy and radiation on testicular and ovarian function [19][20][21][22]. With the exception of the 8.5 Gy findings discussed above, results from present and previous studies showed a radioprotective effect, with longer survivals, when GHRH antagonists were given before doses of less than 10 Gy of whole body radiation (XRT) in C3H mice.…”
Section: Discussionmentioning
confidence: 99%